METHODS FOR COLLABORATIVE PORTFOLIO DEVELOPMENT WITH STUDENTS - Sayidmurodova Shaxlo Otamurod qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores methods for collaboratively developing portfolios with students in educational settings. Collaborative portfolio creation encourages active participation, reflective practice, and shared responsibility in documenting and evaluating creative and academic work. The study highlights strategies that enable students and educators to work together in organizing, analyzing, and reflecting on learning outcomes. Collaborative approaches foster engagement, enhance critical thinking, and promote a deeper understanding of personal and academic growth. The methodology discussed emphasizes communication, feedback, and iterative development as core components of effective collaborative portfolio practices.